Avaliação do desempenho escolar de crianças contaminadas por chumbo - Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Almeida, Christiana Gonçalves Meira de; Pereira, Veronica Aparecida; Capellini, Vera Lúcia Messias Fialho [UNESP] (FapUNIFESP (SciELO), 2014)
The lead contamination in children has been the subject of research in the field of public health. This study evaluated the academic performance of 102 children from first to fourth grade. The subjects were divided into two groups. The first group was composed of 34 children without lead poisoning or with poison at levels lower than 5 µg/dl. The second group was composed of 68 children with blood lead levels between 10 and 40 µg/ dl. The instruments used to evaluate the academic performance were anamnesis and a scholarly performance test called Teste de Desempenho Escolar, TDE. The results indicated better academic performances from the second group with significant differences in arithmetic, reading and general scores. In a comparison between genders, the girls had better performances than the boys. These results were consistent with the parents’ perception in anamnesis. Although other variables were present, the data showed great academic damage for children with higher leadpoison. These outcomes require political policies to control contamination and intervention in this population.

La contaminación de niños por plomo ha sido objeto de investigación en el ámbito de la salud pública. En este estudio se evaluó el desempeño académico de 102 niños de la Enseñanza Fundamental. Los participantes fueron divididos en dos grupos: uno con 34 niños no contaminados o con nivel inferior a 5 µg/dl y el otro, de 68 niños, estaba con nivel de contaminación por plomo en la sangre entre 10 y 40 µg/dl. Para evaluación fueron utilizados el Test de Desempeño Escolar (TDE) y anamnesis. Los resultados indicaron mejor desempeño académico para el segundo grupo, con diferencias significantes en aritmética, lectura y desempeño general. La comparación entre los sexos indicó mejor desempeño para niñas, dato coherente con la percepción de los padres en la anamnesis. Aunque otras variables estén presentes, los datos apuntan perjuicios académicos mayores para niños con índices de plomo más altos. Esas descubiertas requieren políticas públicas para control de la contaminación y reducción de los daños en contaminados.

A contaminação de crianças por chumbo tem sido objeto de investigação no âmbito da saúde pública. Neste estudo avaliou-se o desempenho acadêmico de 102 crianças do Ensino Fundamental. Os participantes foram divididos em dois grupos: um com 34 crianças não contaminadas ou com nível inferior a 5 µg/dl e o outro, de 68 crianças, estava com nível de contaminação por chumbo no sangue entre 10 and 40 µg/dl. Para avaliação foram utilizados o Teste de Desempenho Escolar (TDE) e anamnese. Os resultados indicaram melhor desempenho acadêmico para o segundo grupo, com diferenças significantes em aritmética, leitura e desempenho geral. A comparação entre os sexos indicou melhor desempenho para meninas, dado coerente com a percepção dos pais na anamnese. Embora outras variáveis estejam presentes, os dados apontam prejuízos acadêmicos maiores para crianças com índices de chumbo mais altos. Esses achados requerem políticas públicas para controle da contaminação e redução dos danos em contaminados.
Academic performance evaluation of lead-poisoned children
Evaluación del desempeño escolar de niños contaminadas por plomo
Keywords: Academic performance test; School performance; Public health; Test; Aprovechamiento escolar; Salud pública; Teste; Rendimento escolar; Saúde pública